(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the philosophical impact of social networks on the consciousness of modern society. The essence of the concept of public consciousness is revealed, the relationship between individual and social consciousness is highlighted. Social networks are interpreted as a new social space, and their mechanisms of mass opinion formation, information dissemination, and influence on consciousness are considered. The article analyzes the positive and negative effects of social networks on the consciousness of society from a philosophical point of view, and justifies the need to form an information culture.